2019
DOI: 10.1142/s0217590819420037
|View full text |Cite
|
Sign up to set email alerts
|

Does Foreign Aid Help or Hinder the Institutional Quality of the Recipient Country? New Evidence From the Oic Countries

Abstract: This study examines the impact of foreign aid on the institutional quality (IQ) of the OIC countries. Using the data of OIC countries for the three-year average period from 1991 to 2016, the system GMM finds that aid in general deteriorates the IQ for the aid recipient countries. However, quantile regression suggests that the negative impact of foreign aid on institutional quality (IQ) is relatively greater in the countries where the existing quality of institution is poor. The findings of the study suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Furthermore, Sharma (2012) suggests that the negative relationship might also indicate the existence of a fiscal deficit in the country, thereby reducing private-sector interest in making PPP investments. While previous studies have not confirmed the significance of aid (Kasri & Wibowo, 2015;Sharma, 2012), from a wider perspective, it has been found to reduce the institutional quality in Muslim countries (Chowdhury et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, Sharma (2012) suggests that the negative relationship might also indicate the existence of a fiscal deficit in the country, thereby reducing private-sector interest in making PPP investments. While previous studies have not confirmed the significance of aid (Kasri & Wibowo, 2015;Sharma, 2012), from a wider perspective, it has been found to reduce the institutional quality in Muslim countries (Chowdhury et al, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, the industry can participate as an alternative source of funds to develop public infrastructure in the future. Chowdhury et al (2022) look at institutional quality in OIC countries using OIC country data for a three-year average period from 1991 to 2016 to identify any correlation between aid and institutional quality within a Muslim country. Their study find that aid in its general form reduces institutional quality in Muslim countries.…”
Section: Ictmentioning
confidence: 99%